Konsep Dakwah Efektif - Supriyanto Supriyanto (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2018)
Da'wah is part of an important activity in Islam that seeks to socialize Islamic teachings to the public at large. Da'wah activities become a privilege for Muslims, especially for preachers who have integrity, qualifications, and scientific competence regarding Islam. In order for the da'wah messages delivered by a preacher to people can be understood, accepted, and well-practiced by the wider community, preaching must be effective. Effective da'wah requires a number of qualifications, especially those within the preachers and the mastery of the relevant methods of preaching. This paper tries to decipher the concept of effective da'wah by focusing on the factors of da'wah methods.